The Synergy of School Culture, Academic Supervision, and Work Discipline in Fostering Teacher Well-Being - Fitriyatul Aeni; Dewi Amaliah Nafiati; Suriswo Suriswo (Journal of Educational Sciences, 2026)
Teacher well-being has emerged as a strategic issue in sustaining educational quality amid increasing professional demands and ongoing educational reforms. This study aims to analyze the synergistic roles of school culture, academic supervision, and work discipline in fostering teacher well-being through a library research approach. Data were collected from reputable national and international journal articles, educational policy documents, and scholarly books published within the last decade. The analysis employed content analysis and comparative analysis to synthesize theoretical perspectives and empirical findings. The results indicate that a supportive school culture contributes to psychological safety and social support, which function as protective factors against stress and burnout. Transformative clinical academic supervision enhances teachers’ self-efficacy, professional satisfaction, and motivation through reflective and collaborative practices. Meanwhile, integrity-based work discipline provides role clarity and organizational stability that support emotional balance. The synergy of these three elements forms an integrative managerial ecosystem that promotes sustainable teacher well-being. This study offers a conceptual framework that positions teacher well-being as a systemic organizational outcome rather than merely an individual condition.